Genome-wide analysis of maize OSCA family members and their involvement in drought stress - Ding,Shuangcheng; Feng,Xin; Du,Hewei; Wang,Hongwei (PeerJ, 2019)
Background Worldwide cultivation of maize is often impacted negatively by drought stress. Hyperosmolality-gated calcium-permeable channels (OSCA) have been characterized as osmosensors in Arabidopsis. However, the involvement of members of the maize OSCA (ZmOSCA) gene family in response to drought stress is unknown. It is furthermore unclear which ZmOSCA gene plays a major role in genetic improvement of drought tolerance in Maize. Methods We predicted the protein domain structure and transmembrane regions by using the NCBI Conserved Domain Database database and TMHMM server separately. The phylogeny tree was built by Mega7. We used the mixed linear model in TASSEL to perform the family-based association analysis. Results In this report, 12 ZmOSCA genes were uncovered in the maize genome by a genome-wide survey and analyzed systematically to reveal their synteny and phylogenetic relationship with the genomes of rice, maize, and sorghum. These analyses indicated a relatively conserved evolutionary history of the ZmOSCA gene family. Protein domain and transmembrane analysis indicated that most of the 12 ZmOSCAs shared similar structures with their homologs. The result of differential expression analysis under drought at various stages, as well as the expression profiles in 15 tissues, revealed a functional divergence of ZmOSCA genes. Notably, the expression level of ZmOSCA4.1 being up-regulated in both seedlings and adult leaves. Notably, the association analysis between genetic variations in these genes and drought tolerance was detected. Significant associations between genetic variation in ZmOSCA4.1 and drought tolerance were found at the seedling stage. Our report provides a detailed analysis of the ZmOSCAs in the maize genome. These findings will contribute to future studies on the functional characterization of ZmOSCA proteins in response to water deficit stress, as well as understanding the mechanism of genetic variation in drought tolerance in maize.
Keywords: Phylogenetic analysis; OSCA gene family; Genetic variation; Drought stress; Maize; Expression pattern